2010
DOI: 10.1103/physrevb.81.115443
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally mediated control of single-electron transmission in weakly coupled molecule-metal junctions

Abstract: We propose a mechanism which allows one to control the transmission of single electrons through a molecular junction. The principle utilizes the emergence of transmission sidebands when molecular vibrational modes are coupled to the electronic state mediating the transmission. We will show that if a molecule-metal junction is biased just below a molecular resonance one may induce the transmission of a single electron by externally exciting a vibrational mode of the molecule. The analysis is quite general but r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The acronym refers to the fact that the excitation energy is calculated as the difference between two self-consistent calculations, one traditional ground state calculation and one where an electron is constrained to a certain Kohn-Sham orbital as the system reaches self-consistency. The method is formally justified only when the constrained orbital is the lowest lying of its symmetry [102], but it is often applied in other situations with reasonable success [33,[103][104][105][106]. GPAW implements a generalized version of SCF, where it is possible to constrain an electron to any linear combination of Kohn-Sham orbitals, which is desirable for molecules on surfaces where the molecular orbitals hybridize with substrate states.…”
Section: Scfmentioning
confidence: 99%
“…The acronym refers to the fact that the excitation energy is calculated as the difference between two self-consistent calculations, one traditional ground state calculation and one where an electron is constrained to a certain Kohn-Sham orbital as the system reaches self-consistency. The method is formally justified only when the constrained orbital is the lowest lying of its symmetry [102], but it is often applied in other situations with reasonable success [33,[103][104][105][106]. GPAW implements a generalized version of SCF, where it is possible to constrain an electron to any linear combination of Kohn-Sham orbitals, which is desirable for molecules on surfaces where the molecular orbitals hybridize with substrate states.…”
Section: Scfmentioning
confidence: 99%
“…Electron transport through a molecular tunnel junction has very non-intuitive characteristics. Many experimentalists and theoreticians of molecular science refer to hydrogen molecular transport to be explained by transport through a single channel [23][24][25][26] , instead of the presence of hydrogen molecular bonding and anti-bonding states, as conductance channels. On the basis of the firstprinciple calculations, it has been already reported that the transmission probability through hydrogen molecular tunnel junction becomes exactly one for molecular antibonding state 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Electron transport through molecule has very non-intuitive characteristics. Many experimentalists and theoreticians of nano science refers to hydrogenic molecular transport to be explained by transport through a single channel [3][4][5][6]. K. S. Thygesen et.al [7] presented that transmission through molecular anti-bonding state becomes nearly equal to one, where as they utilize density function theory with wannier function.…”
mentioning
confidence: 99%